2021
DOI: 10.4236/ojog.2021.116063
|View full text |Cite
|
Sign up to set email alerts
|

Tactile and Ultrasound Image Fusion for Functional Assessment of the Female Pelvic Floor

Abstract: Introduction: The true etiology of pelvic organ prolapse and urinary incontinence and variations observed among individuals are not entirely understood. Tactile (stress) and ultrasound (anatomy, strain) image fusion may furnish new insights into the female pelvic floor conditions. This study aimed to explore imaging performance and clinical value of vaginal tactile and ultrasound image fusion for characterization of the female pelvic floor. Methods: A novel probe with 96 tactile and 192 ultrasound transducers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Over the last decade, research has revealed new, expanded knowledge regarding pelvic muscle (PM) complexity, 1 anatomic specificity, physiologic functioning, and potential for specific muscle injury 2 (e.g., tears) or pain 3 (e.g., myofascial). Improved imaging techniques have refined the assessment and identification of the range of PM changes, injuries, and recovery associated with life course events (e.g., childbirth) 4–8 . There remains a need to estimate PM health (optimal to poor) using clinical examination that draws on this new knowledge to support ongoing research and advance clinical care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last decade, research has revealed new, expanded knowledge regarding pelvic muscle (PM) complexity, 1 anatomic specificity, physiologic functioning, and potential for specific muscle injury 2 (e.g., tears) or pain 3 (e.g., myofascial). Improved imaging techniques have refined the assessment and identification of the range of PM changes, injuries, and recovery associated with life course events (e.g., childbirth) 4–8 . There remains a need to estimate PM health (optimal to poor) using clinical examination that draws on this new knowledge to support ongoing research and advance clinical care.…”
Section: Introductionmentioning
confidence: 99%
“…Improved imaging techniques have refined the assessment and identification of the range of PM changes, injuries, and recovery associated with life course events (e.g., childbirth). [4][5][6][7][8] There remains a need to estimate PM health (optimal to poor) using clinical examination that draws on this new knowledge to support ongoing research and advance clinical care. However, standardization of PM assessment including training materials and quality control is lacking.…”
Section: Introductionmentioning
confidence: 99%